Caracterización experimental de un concentrador solar circular fresnel (2024)
in the field of high temperature solar technologies, the Circular Solar Fresnel Concentrator stands out as one of the most used devices to concentrate direct solar irradiation, thus generating a focal area with a large temperature increase